Postnatal diagnosis of maternal congenital heart disease: missed opportunities. (14th September 2015) - Vashisht, Ananya; Katakam, Narmada; Kausar, Samina; Patel, Neena; Stratton, Jane
Abstract : A 30-year-old primigravida with no known comorbidities presented to the emergency department at 29+6/40 gestation, with breathlessness. The initial diagnosis was pulmonary embolism, which was later revised following initial investigations and considered to be pre-eclampsia/HELLP (haemolysis, elevated liver enzymes, low platelets) syndrome. Following caesarean section and delivery of a live baby, the patient had episodes of cyanotic hypoxia and was admitted to intensive care. A provisional diagnosis of idiopathic pulmonary hypertension was performed. Decompensation led to transfer to a specialist intensive care unit for extracorporeal membrane oxygenation, where a diagnosis of patent ductus arteriosus and Eisenmenger's syndrome was made. Heart disease is the leading indirect cause of maternal death, and Eisenmenger's syndrome in pregnancy carries a 50–65% mortality. A literature review demonstrated that this is the only reported case of a postnatal diagnosis of Eisenmenger's syndrome. We considered missed opportunities to make an earlier diagnosis, so that patients and doctors will benefit from the lessons we learnt.